Měkkýši České republiky - Rindtová, Dita (Česká zemědělská univerzita v Praze, Kamýcká 129, 165 21 Praha 6 - Suchdol, http://czu.cz/, 2016)
The Bachelor work Mollusca of the Czech Republic deals with basic information about molluscs occurring in the Czech Republic. In the research part of my work I deal with the anatomy of their bodies, shells and life cycles characteristic for the main representatives. In general characterization the work mentions endangered species listed in the Red List. Furthermore, the research part deals with ecology focused on shellfish incidence depending on the conditions of the ecosystem, introduction, and the methods of mollusc importance to humans. The aim of the practical part was a faunal survey of selected localities contaminated by a man. This research was carried out in selected localities near the town of Příbram. It was the firsta research focused on the incidence of molluscs in these areas. The methodology of sample collection was carried out according to common methods of collecting molluscs and it is more specified in the work. The own research was focused on characterisation of the areas (5 localities) where the collection was carried out. Thus there was formed a systematic overview of acquired kinds of terrestrial representatives according to designated habitats, taxonomic classification and specific characterisation of the species. A total of 514 individuals were processed belonging to 26 species of molluscs. The most numerous family had Vrásenkovití (Discidae) where the number of representatives climbed to 82 individuals. On the contrary Oxychilidae family, Skleněnkovití (Vitrinidae) and Melampovití (Ellobiidae) occured the least. There was found only one individual of each family. In the last part of my work I deal with comparison of my research to the previous research carried out in Kokořínsko Reserve. This area has similar climatic conditions and the features of the ecosystems. The result of the comparison corresponds to the variability of the species found here.
Keywords: biologická diverzita; ulita; Měkkýši; ekologie; sběr; faunistický výzkum